Predicting the next phases for nutrition under COVID-19: Factors to consider in prioritising nutrition interventions - Bouis, Howarth E. (Nutrition Connect, 2020)
As terrible as the direct effects of COVID have been and continue to be, the indirect effects on malnutrition in low-income settings over the next several years will be severe as well. Incomes will likely decline and food prices rise over time. The result will be worsening dietary quality. The implications are clear: we need to take action to mitigate, as much as possible, these predicted negative consequences for nutrition. Now.